A manual of cataloguing practice - Bakewell, K. G. B. (International series of monographs in library and information science ;, 1972)
A Manual of Cataloguing Practice is a text on cataloguing and covers topics ranging from the major cataloguing codes to the subject catalogue, the name catalogue, and cataloguing of special materials. Physical forms of catalogue are also considered, along with the filing and arrangement of catalogue entries; centralized and cooperative cataloguing; the organization of cataloguing; and the relation of cataloguing to modern methods of information retrieval.